Strategy for Accelerating the Development of Male-Class UAV Systems Through the Integration of Autonomous Subsystems and Military Certification Under STANAG-4671 - Gita Amperiawan (Journal of Economics and Business UBS, 2026)
This study is motivated by the technological gap in the development of the Elang Hitam Medium Altitude Long Endurance (MALE) Unmanned Aerial Vehicle (UAV), which has yet to fully comply with the military certification standard STANAG-4671. The objective of this research is to formulate a strategy to accelerate the national UAV development process through the integration of autonomous subsystems and military airworthiness certification. Employing a library research method, this study applies content analysis to recent scholarly literature, technical reports, and official documentation of the Elang Hitam program. Data were systematically examined to identify patterns of system integration and conformity with international standards. The findings reveal that synergy among industry, research institutions, and regulators serves as the primary factor driving the acceleration of national UAV certification and the foundation for advancing Indonesia's technological independence in aerospace defense. In conclusion, achieving operational readiness for Elang Hitam requires a harmonized approach that concurrently advances technological innovation and institutional certification frameworks. The study underscores that the establishment of a coordinated national airworthiness governance system is essential for aligning UAV development with global standards, thereby enhancing Indonesia’s strategic autonomy and interoperability in the global defense landscape.